Digital Marketing Strategy: An Analysis of the Effectiveness of Influencer and Affiliate Endorsements in Promoting Women's Fashion Products - DEWI, I Gusti Ayu Agung Istri Sari; PURNAMAWATI, Ida Ayu Putu Santi (Journal of Tourism Economics and Policy, 2025)
This study aims to analyze the effectiveness of digital marketing strategies through influencer endorsements and affiliate marketing in influencing consumer purchase intention for women's fashion products, as well as to examine the role of brand awareness as a moderating variable. The research employed a quantitative approach with multiple linear regression analysis based on data collected through questionnaires. The findings reveal that influencer endorsements have a significant and positive effect on purchase intention, indicating that an influencer's credibility, attractiveness, and expertise can enhance consumer willingness to purchase fashion products. In contrast, affiliate marketing does not have a significant direct effect on purchase intention. Regarding the moderating effect, brand awareness does not significantly strengthen the relationship between influencer endorsements and purchase intention, but it does significantly enhance the relationship between affiliate marketing and purchase intention. These results suggest that affiliate marketing strategies are effective only when supported by high brand awareness, whereas the influence of endorsements relies more heavily on the personal branding and credibility of the influencer. The managerial implications of this study highlight the importance for women's fashion companies to optimize collaborations with credible influencers and to build strong brand awareness to improve the effectiveness of affiliate marketing strategies.